2020
DOI: 10.1097/md.0000000000023132
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic site discriminates survival benefit of primary tumor surgery for differentiated thyroid cancer with distant metastases

Abstract: The role of primary tumor surgery in the management of differentiated thyroid cancer (DTC) with distant metastases (DM) remains controversial. We aimed to explore the survival benefit of primary tumor surgery in patients with different metastatic sites. A retrospective cohort study based on the SEER database was conducted to identify DTC patients with DM diagnosed between 2010 and 2016. Patients were divided into following 2 groups: surgery and non-surgery group. Propensity score weighting was emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…However, liver (19.5%) and brain (7.9%) metastases were double the prevalence found in the current data of the SEER 9 registry and exhibited less frequency of multiple organ metastases (19%), as was reported in [ 27 ]. Ding et al used the SEER 18 registry (2010–2016) which covered both papillary and follicular TC patients from 18 geographical regions in the United States [ 27 ]. In contrast to our findings, the study of Chen et al [ 19 ] showed higher frequency of brain metastasis than liver.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…However, liver (19.5%) and brain (7.9%) metastases were double the prevalence found in the current data of the SEER 9 registry and exhibited less frequency of multiple organ metastases (19%), as was reported in [ 27 ]. Ding et al used the SEER 18 registry (2010–2016) which covered both papillary and follicular TC patients from 18 geographical regions in the United States [ 27 ]. In contrast to our findings, the study of Chen et al [ 19 ] showed higher frequency of brain metastasis than liver.…”
Section: Discussionsupporting
confidence: 56%
“…Borschitz and his colleagues [ 26 ] revealed lung and bone to be the preferential sites for thyroid cancer metastasis. Similarly, the article published by Ding et al [ 27 ] reported the lungs as the most common site of distant metastasis in differentiated thyroid cancer, representing 47.7% of the population, followed by bone metastasis (24.9%). However, liver (19.5%) and brain (7.9%) metastases were double the prevalence found in the current data of the SEER 9 registry and exhibited less frequency of multiple organ metastases (19%), as was reported in [ 27 ].…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations